2020
DOI: 10.1093/jac/dkaa354
|View full text |Cite
|
Sign up to set email alerts
|

Cloxacillin or fosfomycin plus daptomycin combinations are more active than cloxacillin monotherapy or combined with gentamicin against MSSA in a rabbit model of experimental endocarditis

Abstract: Background In vitro and in vivo activity of daptomycin alone or plus either cloxacillin or fosfomycin compared with cloxacillin alone and cloxacillin plus gentamicin were evaluated in a rabbit model of MSSA experimental endocarditis (EE). Methods Five MSSA strains were used in the in vitro time–kill studies at standard (105–106 cfu/mL) and high (108 cfu/mL) inocula. In the in vivo EE model, the following antibiotic combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…These results contrast with reports describing successful outcomes when using ceftaroline plus daptomycin as salvage therapy, especially in patients with persistent MRSA bacteremia [ 34 , 35 , 36 ]. Although an experimental model of infective endocarditis suggested that cloxacillin plus daptomycin have a synergistic effect [ 37 ], further clinical studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…These results contrast with reports describing successful outcomes when using ceftaroline plus daptomycin as salvage therapy, especially in patients with persistent MRSA bacteremia [ 34 , 35 , 36 ]. Although an experimental model of infective endocarditis suggested that cloxacillin plus daptomycin have a synergistic effect [ 37 ], further clinical studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this alternative could be considered in resistant isolates or when adverse events appear, but not to simplify antibiotic treatment. Taking also account the synergistic activity between daptomycin and beta-lactams [ 83 , 84 , 130 ] fosfomycin [ 85 , 86 , 87 , 88 , 89 , 90 , 91 ] or tigecycline, a combination regimen with high doses seems to be preferable, whereas single therapy with this drug should be used with caution.…”
Section: Therapeutic Choicesmentioning
confidence: 99%
“…Current oral fosfomycin use is limited to uncomplicated urinary tract infections due to limited absorption and intravenous formulation are yet unavailable in the USA. However, fosfomycin has demonstrated utility against MSSA and MRSA endocarditis in combination with daptomycin or imipenem [113][114][115][116] and a study of in vitro and in vivo with the guinea pig model using intraperitoneal fosfomycin demonstrated promising activity against both planktonic and biofilm-forming E. faecalis when the drug was used in combination with gentamicin and daptomycin 117 . Thus, new therapeutic options with this drug could be considered in the future for E. faecalis IE.…”
Section: Fosfomycinmentioning
confidence: 99%